Caracterização de incidências patológicas de um conjunto habitacional do município de Engenheiro Beltrão - Paraná - Leão, Rafael Henrique (2012)
The real state enterprises are products of the industry of the civil construction that counts with incorporators, investors, planners, manufacturers and others. Therefore, they are passive of flaws, that formed an alliance with the bad weather and the maintenance lack can cause pathological incidences. This work had as general objective, to characterize the pathological incidence in a habitation group, and as specific objectives of identifying the main found pathologies, besides comparing the results obtained with other works. The used methodology went a visit to the habitation group, applying a questionnaire per-defined in samples to select the samplings using statistical methods to identify and to separate the results, for later on to aim the main found pathologies. Photos were also accomplished to evidence the found pathologies. The collected data were compiled by type of pathologies. The main found pathologies are associated to the humidity occurrence.